Pengaruh Gaya Belajar dan Media Pembelajaran Digital Berbantuan Quizizz Terhadap Literasi Membaca Siswa Sekolah Dasar - Rahmadani, Annisa; Satriana, Eny; Mukhlis, Mukhlis (Jurnal Ilmiah Global Education, 2025)
The purpose of this study was to determine and describe the influence of visual, auditory, and kinesthetic learning styles through the use of digital learning media assisted by Quizizz on reading literacy of grade V students of Elementary School Cluster II, Somba Opu District. The type of research used in this study is experimental research. The research sample consisted of the experimental class, namely class VA SDN Sungguminasa V, totaling 29 students and the control class, namely class VB SDN Sungguminasa V, totaling 29 students. Data were collected through reading literacy tests, learning style questionnaires, and observation sheets. Data analysis techniques using descriptive analysis techniques and inferential analysis. The results of the study showed that (1) There is an influence of visual learning style through the use of digital learning media assisted by Quizizz on reading literacy of grade V students of Elementary School Cluster II, Somba Opu District, with a significance value (Sig = 0.00) < 0.05. (2) There is an influence of auditory learning style through the use of digital learning media assisted by Quizizz on reading literacy of grade V students of Elementary School Cluster II, Somba Opu District, with a significance value (Sig = 0.01) < 0.05. (3) There is an influence of kinesthetic learning style through the use of digital learning media assisted by Quizizz on reading literacy of grade V students of Elementary School Cluster II, Somba Opu District, with a significance value (Sig = 0.02) < 0.05. (4) Visual learning style has the greatest influence on reading literacy of grade V students of Elementary School Cluster II, Somba Opu District, with a significance value (Sig = 0.00) < 0.05. Based on the research results, it can be concluded that there is an influence of the use of digital learning media assisted by quizizz and learning styles on the reading literacy of grade V students of SD Gugus II, Somba Opu District.